The Education-Science System Is a Factor That Accelerates the Development of Society and Increases Its Efficiency - Yuldasheva Saodat Mamasakhatovna (Zien Journals, 2021)
This article briefly discusses the fact that the system "Education - Science" is a system that is constantly enriched and developed in theory, practice, and its naturalness and purposefulness is a factor that accelerates the development of society, increasing its efficiency
Keywords: Education; upbringing; spirituality; enlightenment